Lamb wave transducers made of piezoelectric macro‐fiber composite. Issue 8 (8th October 2012) - Mańka, Michał; Rosiek, Mateusz; Martowicz, Adam; Stepinski, Tadeusz; Uhl, Tadeusz
ABSTRACT: During recent years, an intensive research activity concerning the application of Lamb waves (LWs) for SHM has been observed. LWs may be generated and sensed using different types of transducers, and their selection is essential for the SHM system's performance. Results of the investigation of three types of transducers based on macro‐fiber composite (MFC) are presented in this paper; two types of commercially available MFC actuators are compared with a novel type of custom‐designed interdigital transducer also based on the MFC substrate. After a short presentation of the piezoelectric transducer designed for SHM applications, details concerning the proposed interdigital transducer design are provided. Beampatterns of the investigated transducers are first compared using numerical FEM simulations, and next, the numerically obtained beampatterns are verified experimentally using laser vibrometry. In the final part of this paper, advantages and disadvantages of the investigated transducers are discussed. Copyright © 2012 John Wiley & Sons, Ltd.